2016
DOI: 10.1115/1.4033996
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Increase in Forming of Advanced High-Strength Steels Effect of Ram Speed Using a Servodrive Press

Abstract: In forming of advanced high-strength steel (AHSS), the temperature increase at die/sheet interface affects the performance of lubricants and die wear. This study demonstrates that finite-element (FE) analysis, using commercially available software, can be used to estimate temperature increase in single as well as in multiple stroke operations. To obtain a reliable numerical process design, the knowledge of the thermal and mechanical properties of the sheet as well as the tools is essential. Using U-channel dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, the developed model did only emulate single-stroke operations. Fallahiarezoodar et al (2016) have investigated the temperature increase in the tool-workpiece interface in U-channel drawing and deep drawing for single as well as multiple strokes. They found that the maximum temperature rise in the tool-workpiece interface reached 120 ˚C in only nine strokes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the developed model did only emulate single-stroke operations. Fallahiarezoodar et al (2016) have investigated the temperature increase in the tool-workpiece interface in U-channel drawing and deep drawing for single as well as multiple strokes. They found that the maximum temperature rise in the tool-workpiece interface reached 120 ˚C in only nine strokes.…”
Section: Introductionmentioning
confidence: 99%